Efficiency of different dental crowding complex treatment methods in children with chronic generalized catarrhal gingivitis and decompensated form of chronic tonsillitis - Koval, Yu. M.; Novikova, Zh. O. (Journal of Education, Health and Sport, 2017)
The method of complex treatment of dental crowding (DC) in children with chronic generalized catarrhal gingivitis (CGCG) and decompensated chronic tonsillitis (DCT) has been substantiated and developed. Therapeutic regimen incorporated coformulated herbal drug “Imupret” with complex activity. The drug was put on before and during orthodontic treatment according to the scheme developed for the prevention and treatment of periodontal tissues chronic inflammatory diseases at the background of DCT. In all age DC children high prevalence of parodontium tissues diseases, mainly CGCG (74.1% by PMA index) and oral cavity poor hygienic condition took place (1.81 by Silness-Loe index). Combination of DC and CGCG at the background of DCT causes a pronounced decrease of main anti-oxidative enzymes (SOD, catalase) in oral cavity fluid in all children under examination. SOD and catalase activity reduced nearly twice - 11.4±1.05 un/ml to 6.98±0.53 un/ml and 5.03±0.47 mk cat/ml to 2.29±0.18 mk cat/ml, correspondingly. “Imupret” use in the complex treatment increases the body’s resistance, in particular, that of oral cavity and pharynx tissues, and prevents the development and progression of inflammatory diseases of periodontal and oropharyngeal tissues at orthodontic treatment by a mean of 20-30%. The most pronounced effect was marked in the group of postpubertal children. “Imupret” increased anti-oxidative enzymes activity, level of nonenzymatic antioxidants of ascorbic acid α-tocopherol in oral fluid of 14-15 y.o. children.